Integrating Organic Fertilizers from Fish Waste and Chicken Manure for Pakchoi (Brassica chinensis) Cultivation and Community Learning: Integrasi Pupuk Organik dari Limbah Ikan dan Kotoran Ayam untuk Budidaya Sawi Pakchoi (Brassica chinensis) dan Pembelajaran Masyarakat - Nur Hidayatullah Romadhon; Vella Rohmayani; Wildhatus Sholihah Rahmadhani3; lihabi; Ajeng Retno Kustianingrum (UNIVERSITAS PGRI MADIUN, 2026)
This study investigated the effect of fish waste fertilizer and chicken manure on the growth of pakchoi (Brassica chinensis). The experiment was carried out in January 2020 at Puskopad Housing, Mojokerto, using a Randomized Block Design (RBD) with three treatments and nine replications, resulting in 27 experimental units. The treatments consisted of control (P1), fish waste fertilizer at 4.5% concentration (P2), and chicken manure at 25 g (P3). Plant height and number of leaves were observed as growth parameters. Data were analyzed using analysis of variance (ANOVA) followed by the Least Significant Difference (LSD) test. The findings indicated that both fish waste fertilizer and chicken manure significantly influenced plant height, whereas no significant differences were observed in the number of leaves. These results suggest that organic fertilizers derived from fish waste and chicken manure can effectively enhance vegetative growth of pakchoi, particularly plant height, while leaf development remains unaffected. The study provides practical insights into the use of organic fertilizers as an alternative to chemical inputs and highlights their potential as an educational medium for promoting sustainable agriculture within communities